(untitled) (Itinera, 2020)
This text aims to rediscover the studies of Giuseppe Turroni, an important Italian critic whose research activity, had focused particularly on photography and cinema. Active expecially in the central decades of the 20th century, Turroni was the first Italian author to have pointed out the need to constitute a photographic criticism and the importance of studying photography also from an aesthetic point of view. Particularly, this text traces the main guidelines of Turroni’s thought about panchromatic photography, the uses that were made of it in the decades between the 19th and 20th centuries, and, above all, focuses attention on the expressiveness and communicativeness of this medium in contemporary society.